CUSTOMERS’ OPINION TOWARDS CSR OF PUBLIC AND PRIVATE SECTOR BANKS IN TIRUNELVELI- A COMPARATIVE STUDY - Kamalam, G; Juliet Issac, J. Kamala (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Banking system plays an important role in the economic development of the country. Today, banks have diversified their activities and are getting into new products and services that include opportunities in credit cards, consumer finance, wealth management, life and general insurance, investment banking, mutual funds, pension fund regulation, stock broking services, etc. All private and public sector banks are keenly concentrated in fulfilling the need of doing CSR and disclosure practices regularly. The level of its impact on customers shall be measured by using some techniques. In the present study the researcher has concentrated on the view and perception of customers and their attitude towards the achievement of CSR of banking sector particularly in the study area and analysed by using statistical tools like percentage analysis, Chi-square test, two independent sample t-test etc.